Finite element analysis modeling of plates versus intramedullary nails in closed comminuted midshaft tibial fractures - El-Desouky Mahmoud Ahmed; Saleh Ayman Ali; Amr Sherif Mamdouh; Barakat Ahmed Samir (SICOT-J, 2022)
Background: Tibial shaft fractures are usually treated by interlocking nails or plates. The ideal implant choice depends on many variables. Aim: To assess the mechanical behavior of interlocking nails and plates in the treatment of closed comminuted midshaft fractures of the tibia using finite element analysis. Material and methods: This is a prospective study of 50 patients with a mean age of 28.4 years with closed comminuted fractures of the midshaft of the tibia. Data evaluation was done by Finite element analysis (FEA). Fixation was revised in two cases. Results: After load application, there were significant differences in both bending (P = 0.041) and strain percent (P = 0.017), reflecting that interlocking nails were superior to plates. There were also significant differences between titanium and stainless-steel materials in bending (p = 0.041) and strain percent (p = 0.017) after applying load, indicating that titanium was superior to stainless steel. Conclusion: Interlocking nails are superior to plates in treating midshaft tibial fractures. The use of blocking screws may be needed in interlocking nails depending on the pattern and extension of the fracture.